(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Language is the main means of communication, without which the existence and development of the human community are impossible. without them, the existence and development of human society are impossible. The whole world is gradually becoming a single multinational community, which is primarily concerned with the process of globalization. We can say with confidence that the 21st century is the age of communication. Learning a foreign language is a long process and requires a lot of effort and effort. A foreign language is a means of communication, knowledge, information, and accumulation. In the modern world, learning a foreign language has dictated the need to master such types of language activities as listening and understanding, reading, and writing by a foreign language speaker.